2020
DOI: 10.3389/fnhum.2020.00126
|View full text |Cite
|
Sign up to set email alerts
|

Agency and Performance of Reach-to-Grasp With Modified Control of a Virtual Hand: Implications for Rehabilitation

Abstract: This study investigated how modified control of a virtual hand executing reach-to-grasp affects functional performance and agency (perception of control). The objective of this work was to demonstrate positive relationships between reaching performance and grasping agency and motivate greater consideration of agency in movement rehabilitation. We hypothesized that agency and performance have positive correlation across varying control modes of the virtual hand. In this study, each participant controlled motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 82 publications
2
26
0
Order By: Relevance
“…We performed two step-wise experiments in light of these aims. In Experiment 1, we replicated the findings of past experiments 11 13 , whereby the sense of agency increases with an increase in apparent task performance due to automation and decreases in the full automation condition. In Experiment 2, we identified the turning point where the participants’ sense of agency decreases to lower than that in the complete control condition.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…We performed two step-wise experiments in light of these aims. In Experiment 1, we replicated the findings of past experiments 11 13 , whereby the sense of agency increases with an increase in apparent task performance due to automation and decreases in the full automation condition. In Experiment 2, we identified the turning point where the participants’ sense of agency decreases to lower than that in the complete control condition.…”
Section: Introductionsupporting
confidence: 78%
“…Interestingly, this observation of the increase in the sense of agency was replicated even when the participants were given instructions about the assistance 12 . In addition, Nataraj et al 13 , by using a virtual reality environment in which the participants controlled a virtual hand to perform reach-to-grasp movements, showed that the sense of agency decreased if modifications in the movement of the virtual hand due to the automation degraded task performance. These results suggest a positive relationship between apparent task performance as modified by automation and the sense of agency in situations where people continuously operate a tool featuring some automation.…”
Section: Introductionmentioning
confidence: 99%
“…Improved motor control may be enacted from training the person to move better independently or with the assistance of a powered device. Regardless of the rehabilitation approach, the person should be cognitively engaged and integrated with the therapeutic platform or the assistive device ( Moore and Fletcher, 2012 ; Nataraj, 2017 ; Nataraj et al, 2020a , b , c ). Improved perception of involvement and control of movement should better ensure continued participation and positive functional outcomes ( Doyle, 2002 ; Behrman et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Agency is naturally implicated with rehabilitation through perception of neuromuscular action and related functional consequences ( Moore and Obhi, 2012 ). Agency contributes to the performance of functional movements such as reaching ( Nataraj et al, 2020c , d ) and is impaired in the presence of neurological disorders ( Jeannerod, 2009 ; Ritterband-Rosenbaum et al, 2012 ). Agency can also be compromised during the use of powered assistive devices, such as exoskeletons ( Hartigan et al, 2015 ) or sensorimotor prostheses ( Antfolk et al, 2013 ; Hebert et al, 2013 ), due to distortions in embodiment ( Kilteni et al, 2012 ; Caspar et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The notable limitation in this study was that we did not explicitly measure agency and directly relate it to performance. Our previous work has made the positive connection between agency and performance [ 16 ] but relied on verbal estimation of randomly presented time-intervals [ 15 ] to assess agency. In this study, subject onus to estimate time-intervals may be prohibitive to the perceptual conditioning we sought to achieve.…”
Section: Discussionmentioning
confidence: 99%